Analisis Yuridis terhadap Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Dikaitkan dengan Mahkamah Konstitusi sebagai Positif Legislator - Ahdi Hidayat; M. Haykel; Rizqi Ulmaliyah Alhaddi; Selsa Selviana; Siva Delvina (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
National implementation must reflect the Constitution's wishes for all citizens. Articles 56 and 57 of Law Number 24 of 2003 concerning the Constitutional Court explained that the Constitutional Court has the authority to review the 1945 NRI Law. The Constitutional Court does not always play a negative role as a legislator in making decisions. In rare cases, developments have led to a transition to the type of Constitutional Court decisions that extend to positive legislation. This research uses a normative legal approach. Research by conducting legal research. The results of this research indicate that the change in Constitutional Court law from negative to positive was based on the need to fill legal gaps and balance legal certainty, justice, and expediency. Constitutional Court Decision 90/PUU-XXI/2023 introduces new regulations that limit the minimum age requirements for presidential/vice presidential candidates, taking into account their experience in office.